Oxytocin as an Indicator of Psychological and Social Well-Being in Domesticated Animals: A Critical Review - Rault, Jean-Loup; van den Munkhof, Marleen; Buisman-Pijlman, Femke T. A. (Frontiers in Psychology, 2017)
Oxytocin is often portrayed as a hormone specific to social behaviour, reflective of positive welfare states and linked to mental states. Research on oxytocin in domesticated animal species has been few to date but is rapidly increasing (in dog, pig, cattle, sheep), with direct implications for animal welfare. This review evaluates the evidence for the specificity of oxytocin as an indicator of: 1. Social, 2. Positive, and 3. Psychological well-being. Oxytocin has most often been studied in socially relevant paradigms, with a lack of non-social control paradigms. Oxytocin research appears biased toward investigating positive valence, with a lack of control in valence or arousal. Oxytocin actions are modulated by the environmental and social contexts, which are important factors to consider. Limited evidence supports that oxytocin’s actions are linked to psychological states; nevertheless whether this is a direct effect of oxytocin per se remains to be demonstrated. Overall, it is premature to judge oxytocin’s potential as an animal welfare indicator given the few and discrepant findings and a lack of standardisation in methodology. We cover potential causes for discrepancies and suggest solutions through appropriate methodological design, oxytocin sampling or delivery, analysis and reporting. Of particular interest, the oxytocinergic system as a whole remains poorly understood. Appreciation for the differences that social contact and group living pose in domesticated species and the way they interact with humans should be key considerations in using oxytocin as a psychosocial indicator of well-being.